DINAMIKA EMOSI DAN STRATEGI MANAJEMEN KONFLIK PADA REMAJA DI LEMBAGA PEMBINAAN KHUSUS ANAK: EMOTIONAL DYNAMICS AND CONFLICT MANAGEMENT STRATEGIES AMONG ADOLESCENTS IN JUVENILE CORRECTIONAL INSTITUTIONS - Sirri Nahzatun Qowimah; Angellina Anastasia Halim; Mary Philia Elisabeth; Jefri Setyawan (LPPM Universitas Abdurrab, 2026)
Adolescents undergoing rehabilitation in Juvenile Correctional Institutions (Lembaga Pembinaan Khusus Anak [LPKA]) face complex emotional and social conflicts due to their history of legal violations, environmental stressors, and separation from family. Inability to manage emotions and conflicts can hinder the rehabilitation process and increase the risk of maladaptive behaviors. This study aims to explore the emotional dynamics and conflict management strategies of adolescents in LPKA Blitar. Using a descriptive qualitative approach and thematic analysis, data were collected through in-depth interviews, participatory observations, and a series of emotion-based intervention activities. The interventions involved conflict simulation exercises, 4-7-8 breathing techniques, symbolic reflection using visual media such as the